2014
DOI: 10.1111/1467-9477.12025
|View full text |Cite
|
Sign up to set email alerts
|

Voters' Perceptions of Policy Convergence and the Short‐term Opportunities of Anti‐immigrant Parties: Examples from Sweden

Abstract: In contrast to previous studies on the political opportunity structures of anti‐immigrant parties, this article argues that voters’ perceptions of policy convergence between mainstream alternatives affect their short‐term propensity for supporting such partisan challengers. Drawing upon leading research in the field, two hypotheses about voters’ perceptions of policy convergence, in two policy areas (economic redistribution and immigration), are presented. The main findings in the article suggest that policy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Previous studies have found that the Swedish case corroborates the suggestions made by Meguid (2005Meguid ( , 2008, that strategic choices of mainstream parties do affect the electoral success of the radical right (Loxbo 2014). The dismissive issue strategy dominated the behavior of Swedish mainstream parties until 2010, a fact which seems to have reduced the support for the SD (Dahlström & Esaiasson 2013, Heinze 2018.…”
Section: The Swedish Casesupporting
confidence: 59%
See 4 more Smart Citations
“…Previous studies have found that the Swedish case corroborates the suggestions made by Meguid (2005Meguid ( , 2008, that strategic choices of mainstream parties do affect the electoral success of the radical right (Loxbo 2014). The dismissive issue strategy dominated the behavior of Swedish mainstream parties until 2010, a fact which seems to have reduced the support for the SD (Dahlström & Esaiasson 2013, Heinze 2018.…”
Section: The Swedish Casesupporting
confidence: 59%
“…The disengagement has also been expressed as a solid cordon sanitaire -a blocking coalition between most or all of the mainstream parties, Downs (2001) -and as a demonization of the SD (Heinze 2018, Dahlström & Esaiasson 2013, Loxbo 2014, Saveljeff 2011.…”
Section: The Swedish Casementioning
confidence: 99%
See 3 more Smart Citations